Sustainable Business Model in Small and Medium-Sized Enterprises: A Study in Yogyakarta and Magelang - Octavia Lhaksmi Pramudyastuti; Chaidir Iswanaji; Supanji Setyawan; Atika Atika; Alex Johanes Simamora (Universitas Muhammadiyah Ponorogo, 2023)
This study aims to analyze Yogyakarta and Magelang Small and Medium-Sized Enterprises (hereafter) SMEs based on sustainable business model implementation. This study gives new evidence of Yogyakarta and Magelang SMEs’ businesses based on sustainable business model where Indonesian SMEs’ experience the economic crash of Covid-19. This study uses a qualitative descriptive method. Specifically, uses method of qualitative evaluative where this study evaluates SMEs business process by using sustainable business model. Research sample includes 40 SMEs in Yogyakarta and Magelang. Evaluation of SMEs’ business is based on elements of sustainable business model including key partner, key activity, key resources, value proposition, customer relationship, channels, customer segment, cost structure, revenue stream, cash flow management, pivoting plan, and ecological concern. This study uses a “yes and no” questionaries with 13 questions that refers to the elements of sustainable business. Based on the result, this study finds that most SMEs in Yogyakarta and Magelang, implement the elements of a key partner, key activity, key resources, value proposition, customer relationship, channels, cost structure, pivoting plan, and ecological concern. On the other hand, most SMEs do not implement elements of customer segment, revenue stream, and cash flow management. Socialization and special training is needed from various parties related to the implementation of sustainable business models for SMEs.